An investigation of a high-performance centrifugal compressor with a variable map width enhancement slot for proton exchange membrane fuel cell systems in commercial vehicle application. (January 2021) - Jin, Jianjiao; Pan, Jianfeng; Lu, Zhigang; Wu, Qingrui; Xu, Lizhong
Maintaining required performance and rated power output of proton exchange membrane fuel cells while reducing fuel consumption demands and improving efficiencies at the largest parasitic work loss contributor, namely the air compressor. In this paper, we built a high-efficiency one-dimensional match model of centrifugal compressor for proton exchange membrane fuel cells first, which was based on the fuel cell air supply system and the optimal trim factor. And then a variable map width enhancement slot design adjusted by a closed ring was first introduced to extend the surge margin and keep high efficiency. Finally, the compressor with a variable map width enhancement slot was validated at a compressor performance rig and a fuel cell simulation system. The results from compressor performance test rig indicate that the compressor peak efficiency is as high as 77% and the surge margin is enhanced by about 28.1∼ 42.7 %. The simulation results of the fuel cell system indicate the maximum power consumption of the compressor and the H2 consumption of comprehensive adapted world transient vehicle cycle are reduced by nearly 1.6 kW and 4.86%, respectively, in comparison with the baseline screw compressor.